Gestión operativa-administrativa y su incidencia en la planificación y comercialización de maíz de la empresa Sancamilo S.A. de la ciudad de Quevedo, año 2014, Plan de marketing. - Cárdenas Molina, Carmen Virginia (2016)
The production of hard yellow corn (crystal type) that occurs in Ecuador, is of excellent quality for the balanced development of industries and for human and animal consumption, for its high content of fiber, carbohydrates, food and carotene. It is also used as the main raw material for manufacturing pharmaceuticals and industrial products, the high level of performance in milling. Los Rios province has the largest production of corn (56%), has a productivity of 4.56 tonnes / ha and with the largest harvested area, 150,000 hectares, according Situation Bulletin of the Ministry of Agriculture and Livestock Aquaculture and Fisheries, 2013. This research was made into a grain trader SANCAMILO SA who began operations in the year 2010 in the city of Quevedo, located at Km. 4.5 Via Quevedo-Valencia, this company is dedicated to the purchase of wet and dirty commercial grain (corn and soybean) and then transform it into product clean, dry, Grade 1 and 2 (human and animal consumption). This research proposes the marketing plan SANCAMILO Company SA, in order to count on a tool that will help us to provide the commercial behavior of the company for a period of time, to develop activities efficiently, focused the fulfillment of the objectives in the planning and marketing of corn. It also will guide the development of the activities of any area within the Organization, and achieve institutional goals and objectives.